Illocutionary Speech Acts and Types of Hate Speech in Comments on @Indraakenz’s Twitter Account - Anisa Dara Oktaviani; Oktavia Surya Nur (Universitas Sebelas Maret, 2022)
This study aims to analyze illocutionary speech acts and types of hate speech in comments on @indraakenz's Twitter account because of the polemic in his post about being born poor is a privilege. It’s caused a polemic because of a misperception of the meaning of Privilege. That utterance is considered to have no human value because essentially people who are born poor do not have special rights. In this study, the illocutionary speech act theory proposed by Searle was used to analyze the types of speech acts in the comments column of Indraakenz's account. Searle (1976) mentions five illocutionary acts: assertive, directive, expressive, commissive, expressive, and declarative. The results are then classified into types of hate hatred based on the Circular Letter of the Chief of Police Number SE/6/X/2015 to find out the types of hatred that most often arise. The method used in this research is descriptive analysis. In this study, it was found that the type of hatred that often appears is like. The conclusion is the type of hate in the comments is aimed at insulting the honor and reputation of the account owner so that s(he) feels ashamed.